CREATING A PROLONGED FORM OF ACETYLSALICYLIC ACID: AN EXPERIMENTAL APPROACH - V. I. Sevastianov; V. K. Popov; V. Yu. Belov; S. V. Kursakov; E. N. Antonov; S. E. Bogorodsky (Вестник трансплантологии и искусственных органов, 2016)
Aim. The development of a prolonged form of acetylsalicylic acid (ASA) encapsulated into polymeric highly porous microcarriers using supercritical carbon dioxide and the subsequent study of ASA release kinetics in vitro and in vivo using high-performance liquid chromatographic (HPLC).Materials and methods. As polymeric carriers for ASA encapsulation amorphous D,L-polylactides (PLA) and polylactoglycolides (PLGA) of PURASORB PDL02 and PDLG7502 series (PURAC Biochem BV, Netherlands) were selected. The ASA encapsulation was performed using the PGSS (Particles from Gas Saturated Solutions) method of supercritical fl uid formation of microfi ne (20–50 μm) bioresorbable powders of aliphatic polyethers containing 10 wt.% ASA. The release kinetics of ASA from polymeric microparticles into saline solution as well as pharmacokinetic studies in vivo (rabbits) were registered by HPLC.Results. A method of quantitative determination of ASA and its main metabolite salicylic acid (SA) in model solution and blood plasma by HPLC-UV detection with enhanced sample preparation and selectivity was developed. The method’s analytical range without accounting for dilution was 0.05–5.0 μg/ml for model solution and 0.2–10.0 μg/ml for blood plasma; the degree of extraction of ASA SA from blood plasma – 95.8 and 98.1%, respectively. It was demonstrated that the amount of ASA released from PLA during the fi rst 4 h exceeds the mass of ASA released from PLGA by approximately 25% which may serve as a justifi cation for the selection of PLGA as a carrier for the creation of a prolonged form of ASA. Pharmacokinetic studies (rabbits, n = 3) demonstrated a gradual release of ASA from PLGA microparticles during 24 h after intramuscular implantation of encapsulated form of ASA at the dose of 10 mg/kg.Conclusion. Test samples of highly porous microfi ne powders of PLGA obtained by PGSS containing up to 10 wt.% ASA may serve as source prototypes for the development and creation on their basis of a prolonged form of ASA.